PENGARUH PROFITABILITAS DAN STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN - Dinata, I Made Agus Surya; Yadnya, I Putu (E-Jurnal Manajemen, 2014)
Maximizing the value of the company is the ultimate goal of the company. Benchmark value of the company is the owner's welfare. Company's dividend policy will greatly affect the well-being of the owner, so that the necessary unification of interests between management companies and other parties that include shareholders and stakeholders in policydecision company. This study discusses the effect of profitability and ownership structure on firm value and dividend policy as an intervening variable. 156 manufacturing companies in Indonesia Stock Exchange is the population in this study. In conclusion profitability and ownership structure variables affect the dividend policy is positive and significant, dividend policy affects firm value is positive and significant, while profitability and ownership structure has no significant effect on firm value. Keywords: dividend policy and firm value
Keywords: dividend policy and firm value